Successful management of Ellis III coronary perforation and complex bifurcation lesion of the right coronary artery in a patient with high- risk coronary anatomy. A case report - Velarde-Acosta, Kevin (2023)
Complex coronary lesions represent challenging findings for percutaneous coronary intervention and potentially lead to complications during their approach. We present the case of a patient with decompensated heart failure of ischemic origin who presented multiple complex lesions on coronary angiography. The initial approach to the marginal artery was complicated by a severe coronary perforation that was satisfactorily resolved and in the second moment, a bifurcation lesion of the right coronary artery was successfully treated using the inverted Culotte technique.